Circular RNA in Acute Central Nervous System Injuries: A New Target for Therapeutic Intervention - Zhang, Li; Li, Zhenxing; Mao, Lei; Wang, Handong (Frontiers in Molecular Neuroscience, 2022)
Acute central nervous system (CNS) injuries, including ischemic stroke, traumatic brain injury (TBI), spinal cord injury (SCI) and subarachnoid hemorrhage (SAH), are the most common cause of death and disability around the world. As a kind of non-coding ribonucleic acids (RNAs) with endogenous and conserve, circular RNAs (circRNAs) have recently attracted great attentions due to their functions in diagnosis and treatment of many diseases. A large number of studies have suggested that circRNAs played an important role in brain development and involved in many neurological disorders, particularly in acute CNS injuries. It has been proposed that regulation of circRNAs could improve cognition function, promote angiogenesis, inhibit apoptosis, suppress inflammation, regulate autophagy and protect blood brain barrier (BBB) in acute CNS injuries via different molecules and pathways including microRNA (miRNA), nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), ph1osphatidylinositol-4,5-bisphosphate 3-kinase/protein kinase B (PI3K/AKT), Notch1 and ten-eleven translocation (TET). Therefore, circRNAs showed great promise as potential targets in acute CNS injuries. In this article, we present a review highlighting the roles of circRNAs in acute CNS injuries. Hence, on the basis of these properties and effects, circRNAs may be developed as therapeutic agents for acute CNS injury patients.